Level of awareness on the legal implications of plagiarism among adult learners: a case study of public and private universities in Johor and Melaka /Alizah Ali, Rohani Jangga and Nora Mohd Basir - Ali, Alizah; Jangga, Rohani; Mohd Basir, Nora (UiTM Cawangan Johor, 2018)
Academic dishonesty has been proven to be found at all levels of schooling from grade school to graduate school due to the convenient accessibility of electronic resources on the Internet. It is a growing problem at postsecondary institutions. Academic dishonesty can be defined as dishonest behavior related to academic achievement including cheating, plagiarism, lying, deception and any other form of advantage unfairly obtained by one student over the others. Academic dishonesty may be more prevalent in the near future as universities offer more courses through online distance education. In this research we gathered data concerning the level of awareness on plagiarism and level of awareness on the legal implication of plagiarism among 100 respondents who are adult learners at universities which offer distance education in Malaysia. We conclude that raising awareness about plagiarism might be worthwhile it is no substitute for systematic detection and vigilant enforcement among adult learners.